"Eat clean, train mean, get lean": Body image and health behaviours of women who engage with fitspiration and clean eating imagery on Instagram. (September 2022) - Wu, Yu; Harford, Jane; Petersen, Jasmine; Prichard, Ivanka
Abstract: The present study examined the relationship between posting or viewing fitspiration and clean eating imagery in relation to body image, disordered eating, and compulsive exercise among women. Participants (269 women aged 18–30 years) who posted and/or viewed fitspiration, clean eating or travel imagery on Instagram completed an online cross-sectional questionnaire. Results showed engaging with fitspiration and clean eating material (either posting or viewing) was significantly positively associated with increased levels of compulsive exercise and athletic-ideal internalization. However, only viewing (not posting) fitspiration and clean eating content was significantly related to thin-ideal internalization and disordered eating symptomatology. Athletic-ideal internalization mediated the relationships between posting fitspiration/clean eating and disordered eating symptomatology and compulsive exercise. Both thin-ideal internalization and athletic-ideal internalization mediated the relationship between viewing fitspiration/clean eating material and disordered eating and compulsive exercise. Overall, the findings suggest that viewing fitspiration and clean eating content on Instagram is negatively associated with thin-ideal internalization and disordered eating symptomatology, however the same relationships do not exist for people who frequently post these types of material. The mediational pathways provide a nuanced understanding of how engaging with fitspiration and clean eating material on social media influences female users' body image and health behaviour. Highlights: Viewing fitness/eating images on Instagram was linked to greater disordered eating. Posting/viewing fitness/eating content was linked to greater compulsive exercise. Internalization of appearance ideals mediated these relationships. Negative relationships were stronger for viewing than posting.